Faktor yang Berhubungan dengan Kemandirian Lansia di Desa Tamilouw Kecamatan Amahai Kabupaten Maluku Tengah - Windarti Rumaolat; Idham Soamole; Sahrir Sillehu (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2023)
The independence of the elderly is caused by limited physical activity and a reduction in the role of the body which can no longer function fully as a result of requiring good physical health status and also support from the family. To find out the factors related to the independence of the elderly in the village of Tamilouw, Amahai District, Central Maluku Regency. This study uses a quantitative descriptive design, with a cross-sectional approach. A sample of 69 respondents was selected by purposive sampling technique. The research instrument used a questionnaire and the KATZ index to see the independence of the respondents. Data processing uses the chi-square test with a significance level (p- 0.05). This study identified the variables of physical health (p. value = 0.192), family emotional support (p. value = 0.041), family information support (p. value = 0.000), family instrumental support (p. value = 0.004) and appraisal support (p. value = 0.018). Physical health factors are not related to the level of independence of the elderly while factors of emotional support, information, instrumental, and family assessment are strongly related to the level of independence of the elderly.